The Role of Theory and Policy in the Educational Treatment of Language Minority Students: Competitive Structures in California - Tom T. Stritikus; Eugene Garcia (Arizona State University, 2003)
For teachers, theories play a central role in guiding the intellectual work that they have chosen to perform. Teachers are guided by both theories which they use to interpret, analyze and take action in their professional worlds. At any given time, teachers may be faced with multiple and competing theoretical perspectives which attempt to influence their classroom practice. In this article, we examine the theoretical and policy-based positions currently competing to shape the nature of educational practice for language minority students. We highlight the salient theoretical differences between additive and subtractive conceptions for the education of language minority students and their policy- and practice-based implications. Then, we examine select findings from one district's implementation of Proposition 227, and consider how teachers react when competing theories attempt to shape their classroom practice. Specifically, we consider: How might teachers' theories be complemented or contrasted by the underlying theoretical position of Proposition 227? How do teachers' theories about their students mediate the manner in which they react and respond to the policy shift away from native language instruction? We conclude by considering what implications additive and subtractive competitive structures have for the future of policy and practice for language minority students in the United States.